Analisis Kebutuhan Stake Holder - Purwatiningsih, Dyah Retno; Handayani, Dwi Iryaning; Kessy, Annisa; Masudin, Ilyas (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
The development of an industry in 2008 is very different with 13 years ago so that, need the reobservation on the curriculum. The graduate of Industrial Engineering of University of Muhammadiyah Malang can compete with the raduate from other university and can get the job. That is why the Industrial Engineering need to know the criteria and the necessity that the stake holder want in the development of industry, and the result of it can be use as the reference in the development of the curriculum in industrial technical. So that the graduate of industrial technical is realy appropirate with the stake holder want and ready to compete with other graduate from other private university. The aim of this research is to get the curriculum attributetha appropriate with the necessity of todays stake holder. Analytical hierarchy process (AHP) is use as the theory in this research. The criteria that the stake holder want in the service sector or manufacture sector are proffesion skill, managerial, interesting appearance, communication skill, computer ability, meanwhile the criteria for the private enterprise are discipline, modal, skill, creative, team work.